China’s Clean Heating Policy and Effects on Blood Pressure in Rural Beijing Adults - Talia Sternbach; Sam Harper; Xiaoying Li; Collin Brehmer; Yuanxun Zhang; Wenlu Yuan; Shu Tao; Kaibing Xue; Kennedy Hirst; Guofeng Shen; Christopher Barrington-Leigh; Xiang Zhang; et al. (Environmental Health Perspectives, 2026)
Abstract Large-scale residential energy transitions from solid fuel to clean energy are promising strategies to mitigate climate change and improve population health, but rigorous evaluation of their impacts is rare. China’s Clean Heating Policy (CHP) aimed to transition tens of millions of households from coal to electric and gas-based space heating. Following evidence of policy-driven improvements in indoor air pollution and indoor temperature, we evaluated the CHP’s impact on blood pressure (BP). In winter 2018–2019, we enrolled 1,003 adults aged >40 years from 50 Beijing villages not yet treated by the CHP; 20 villages were treated during follow-up (winters 2019–2020 and 2021–2022). Brachial and central BP and covariates were measured during household visits by trained staff. Policy impacts were estimated using an extended two-way fixed-effects difference-in-differences approach with village-clustered standard errors and adjustment for key BP predictors to improve precision. We found evidence of reductions (in mmHg) in brachial systolic BP (−1.4, 95% confidence interval [CI]: −3.3, 0.5), central systolic BP (−1.5, 95% CI: −3.3, 0.4), brachial diastolic BP (−1.6, 95% CI: −2.9, −0.3), and central diastolic BP (−1.6, 95% CI: −2.9, −0.3) among villages treated by the CHP compared with those untreated. Treatment effects varied by the year villages were treated by the CHP (p for homogeneity = 0.00 to 0.14) with greater BP reductions among participants in earlier-treated villages. Household energy policies like the CHP may serve as effective population-level interventions to reduce BP in China and complement high-risk cardiovascular prevention strategies.